2021
DOI: 10.1177/0887302x211004892
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Fear and Weight Gain: Effects on Overweight and Obese Adults’ Purchasing Exercise Apparel Online

Abstract: The purpose of this study was to investigate the interactive effect of pandemic fear and weight gain on overweight and obese consumers’ decisions to purchase exercise apparel online based on the theory of planned behavior and body-related self-discrepancy theory. A sample of 515 male and female adults with BMIs of 25 and higher participated in this study. The effect of pandemic fear on the attitudes toward purchasing exercise apparel online was only positive for overweight and obese consumers who did not gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
4
0
3
Order By: Relevance
“…Individuals buy digital items online to reduce self-discrepancy, thereby enhancing their self-esteem ( Li et al, 2019 ). It is found that self-discrepancy moderates the relationship between pandemic fear and online shopping intention ( Shin, 2021 ). People’s concerns about the COVID-19 pandemic have a positive effect on their online shopping intention, while this positive relationship is stronger among those with greater self-discrepancy.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals buy digital items online to reduce self-discrepancy, thereby enhancing their self-esteem ( Li et al, 2019 ). It is found that self-discrepancy moderates the relationship between pandemic fear and online shopping intention ( Shin, 2021 ). People’s concerns about the COVID-19 pandemic have a positive effect on their online shopping intention, while this positive relationship is stronger among those with greater self-discrepancy.…”
Section: Resultsmentioning
confidence: 99%
“…Persebaran Penggunaan Aplikasi Kesehatan Global Berdasarkan gambar 1, saat ini Indonesia menempati urutan ke 3 penggunaan aplikasi layanan jasa kesehatan di dunia mengalahkan Amerika dan Inggris. Saat pandemi terjadi perilaku konsumen berubah dengan adanya rasa takut yang timbul karena adanya virus corona, konsumen lebih memilih untuk berbelanja atau melakukan sesuatu secara online dirumah untuk mengurangi rasa cemas [13]. Dalam kasus perubahan perilaku konsumen karena adanya kasus COVID-19 yang meningkat menimbulkan ketakutan masyarakat untuk datang ke rumah sakit menggunakan layanan jasa dokter secara langsung [14].…”
Section: Pendahuluanunclassified
“…Present research also contributes to the literature on e-commerce the analysis of current changes in customers behavior in on-line environment. It also complements the literature with the actual trends (Shin, 2021;Chakraborty et al, 2022) in developing and growth observed in e-commerce. It fulfils the gap shown in the literature, where was examined that among the business focuses on a short-term goal and needed results immediately, further empirical analysis and research-proven cases need to be accomplished (Fedushko & Ustyianovych, 2022).…”
Section: Discussionmentioning
confidence: 86%